Bild-Konzeptionen in Bilderbibeln und Kinderbibeln: die historischen Anfänge und ihre Wiederentdeckung in der Gegenwart - Keuchen, Marion (Die Bibel in der Kunst, 2019)
The Children's Bible as one of the central mediums in the history of Protestant religious education has only come into the focus of research during the last three decades. It is astonishing that the picture as a striking element of this genre has hardly been explored so far. The author addresses this research gap and develops an analytical apparatus. This permits the examination of image concepts in relation to the complete work or to an individual image using functional differentiations. The illustration concepts the author has developed contribute to a new and - sometimes - surprising interpretation of the imagery of old and new illustrated bibles ("Bilder-Bibeln") and Children's Bibles in contexts of religious education.